2010
DOI: 10.1063/1.3405757
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment at the BaCuSeF/ZnTe interface

Abstract: In situ photoemission spectroscopy experiments are used to characterize the interface between ZnTe and the wide band gap p-type semiconductor BaCuSeF. The contact is characterized by a null valence-band offset, a large conduction-band offset, and a chemically graded interface. By applying the transitivity rule for band offset and on the basis of similarities in chemical composition, BaCuSeF contact to chalcogenide photovoltaic absorber materials would be expected to have similar properties. By extension, BaCuC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Indeed, applying LaCuOSe:Mg epitaxial thin films as the anode layers in OLEDs has yielded a rather low hole injection barrier (∼0.3 eV). 7 More recently, similar works have extended this strategy to include copper selenide grown at room temperature 8,9 and BaCuFSe 10,11 because their valence band maximum (VBM) structures are similar to that of LaCuOSe and are composed of antibonding states of Cu 3d and Se 4p admixed orbitals. [12][13][14][15][16] Although we demonstrated that LaCuOSe can be applied to optoelectronic devices such as OLEDs 7 and excitonic blue LEDs, 17 the carrier transport/doping mechanism is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, applying LaCuOSe:Mg epitaxial thin films as the anode layers in OLEDs has yielded a rather low hole injection barrier (∼0.3 eV). 7 More recently, similar works have extended this strategy to include copper selenide grown at room temperature 8,9 and BaCuFSe 10,11 because their valence band maximum (VBM) structures are similar to that of LaCuOSe and are composed of antibonding states of Cu 3d and Se 4p admixed orbitals. [12][13][14][15][16] Although we demonstrated that LaCuOSe can be applied to optoelectronic devices such as OLEDs 7 and excitonic blue LEDs, 17 the carrier transport/doping mechanism is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, applying LaCuOSe:Mg epitaxial thin films as the anode layers in OLEDs has yielded a rather low hole injection barrier (∼0.3 eV) . More recently, similar works have extended this strategy to include copper selenide grown at room temperature , and BaCuFSe , because their valence band maximum (VBM) structures are similar to that of LaCuOSe and are composed of antibonding states of Cu 3d and Se 4p admixed orbitals. …”
Section: Introductionmentioning
confidence: 99%
“…Zakutayev et al [55] investigated the interface formed by ZnTe and the wide-gap material BaCuSeF. Zakutayev et al [55] investigated the interface formed by ZnTe and the wide-gap material BaCuSeF.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…3 According to photoelectron spectroscopy measurements, surface oxidation decreases the BaCuChF work function 45 which inhibits ex-situ processing of this material in thin film solar cells. 2,46 The combination of oxidized grain boundaries and anisotropic crystal structure causes a 27 fold decrease in mobility of polycrystalline BaCuTeF thin films compared to the c-axis oriented epitaxial samples. 28 Since the ratio of average to in-plane effective mass is 3, 26 the additional factor of 9 must stem from the difference in the carrier mean free path in This conclusion provides chemical guidance for the design of polycrystalline p-type transparent chalcogenides with mobility of free holes suitable for optoelectronic applications.…”
Section: E Oxygenmentioning
confidence: 99%
“…BaCuChF (Ch = S, Se, Te) is a family of p-type transparent conductors 1 suitable for contact applications in thin film solar cells 2 and organic light-emitting devices. 3 These fluorochalcogenides are isostructural 4,5,6 with the oxychalcogenide p-type transparent conductors LnCuOCh (Ln = La, Pr, Nd) 7 and the oxypnictide high-temperature superconductors LaFeOPn (Pn = P, As, Sb) 8 (Fig.…”
Section: Introductionmentioning
confidence: 99%